Fenomena Kepemimpinan di Sekolah dan Madrasah - Anjar Sri Wahyuni (Jurnal Pembelajaran dan Ilmu Pendidikan, 2023)
The success of an educational institution is highly dependent on the leadership of the principal or madrasah. Because the principal of the school / madrasah is a leader in the institution, the principal must be able to bring the institution towards the achievement of the goals that have been set, the principal must be able to see changes and be able to see the future in a better global life. Schools or madrasahs are complex and unique institutions. It is complex because the school is an organization in which there are various dimensions which are interrelated and determine each other. Meanwhile, its unique characteristic is that it shows that the school as an organization has certain characteristics that are not shared by other organizations. The characteristics that place the school have its own character, where there is a teaching and learning process, a place for the cultivation of human life. In accordance with the characteristics of the school as a complex and unique organization, the duties and functions of the principal should be seen from various points of view. In addition to carrying out managerial duties, the principal plays an important role in taking leadership in order to advance teaching. Madrasas as Islamic educational institutions in their development process have experienced management strategies with changing goals that are adapted to the conditions of the times. In the days before the proclamation of independence, madrasas were managed for the purpose of the afterlife, which was in a far different position from the education established by the Dutch government, which directed programs towards the intellectuality of their students. This expenditure on the school system further widens the gap between the output or production of madrasah education. As a result, civic life has resulted in differences in the quality of life among Indonesian citizens, attitudes and ways of thinking and orientation experience very striking differences in one Dutch product which is secular and intellectual in its attitude and mindset, on the other hand the product of madrasa education is life-oriented madrasa education. the afterlife and ignore worldly life. Madrasah education, which is characterized by Islam, is likely to remain attractive as a material for academic study. This is based on the consideration that madrasa education is a representation of the capital of Islamic education in Indonesia as an Islamic education, so madasas basically have an explicit mission that madrasas actually carry a big mandate which they embody and will somehow reflect the image of Islam itself. Social factors that influence progress are the sources of funds available in the community and often provided by local governments. A madrasah environment that varies in social and economic conditions with good local governments that have good natural resources and taxes will certainly have an effect on the progress of education in madrasah